Sediment Core from the Seafloor of Aru Trough, West Papua - Indonesia - Dida Kusnida; Tommy Naibaho (Jurnal Geologi dan Sumberdaya Mineral, 2018)
Results of multi-sensor core logger measurement of single sediment core from the Aru Trough are presented in this paper. In this study an effort is to depict the general pattern of seafloor sediment over the study area to its physical characteristics. Microscopic observations of sediments extracted from the top and bottom of the core in general show the presence of shell fragments and foraminiferas (f), mafic minerals (m) and organic residuals of blackish-brownish lignite (l). The physical characteristics of sediment core indicate that the cps value of natural gamma measurement with range of 32-38 is interpreted associated with terrigenous sediment type transported and deposited on the seafloor. Magnetic susceptibility graph spikes of core sample located at depth of 180-185 cm and 195-200 cm of darker sandy silt lens seems to have more prominent values compared to the uniform background values and also indicate that the sediment fill derived and associated with the terrigenous sediment type. The gradually change of velocity gradient in the interval between 45 and 226 cm may reflect a change from a relatively consolidated sediments above 45 cm to poorly consolidated sediments below 45 cm. XRF data show that Th/U ratios = 1.44 (